KEANEKARAGAMAN DAN DISTRIBUSI JENIS JAMUR MAKROSKOPIK DI TAMAN HUTAN RAYA POCUT MEURAH INTAN, ACEH, INDONESIA - Kusuma, Hendrix; Harnelly, Essy; Thomy, Zairin; Itawarnemi, Hilmina (Biotik, 2025)
Data on the diversity of macroscopic fungi in Tahura Pocut Meurah Intan is still not widely available, resulting in a gap in basic data that is essential for conservation, area management, and exploration of biological potential. This study aims to identify the diversity of macroscopic fungal species found in PMI National Park and analyze their distribution based on substrate type and habitat conditions. An exploration survey method was used by following existing hiking trails. Fungal samples found in the field were documented, collected, preserved, and then analyzed morphologically. Data analysis was performed using descriptive qualitative methods, presenting species distribution according to habitat conditions, substrate type, and differences between the rainy and dry seasons. Each category was presented as a percentage of the total identified species. 123 macroscopic fungal species were found, with a dominance of the order Agaricales (39%). A total of 28 species have the potential as alternative food sources, while 17 species have the potential as medicine. The highest diversity was found in habitats with heterogeneous vegetation (85.37%), followed by homogeneous forests (21.95%) and agricultural areas (16.26%). Weathered wood was the main substrate where fungi grew (56%), and the number of species was higher in the rainy season than in the dry season. These findings indicate that the PMI Nature Reserve is an important habitat for macroscopic fungi with variations in distribution influenced by differences in substrate and environmental conditions. Keyword: diversity of species, macrofungi, Tahura Pocut Meurah Intan, fungal composition